Pyrrolidine Dithiocarbamate (PDTC) Attenuates Cancer Cachexia by Affecting Muscle Atrophy and Fat Lipolysis - Miao, Chunxiao; Lv, Yuanyuan; Zhang, Wanli; Chai, Xiaoping; Feng, Lixing; Fang, Yanfen; Liu, Xuan; Zhang, Xiongwen (Frontiers in Pharmacology, 2017)
Cancer cachexia is a kind of whole body metabolic disorder syndrome accompanied with severe wasting of muscle and adipose tissue. NF-κB signaling plays an important role during skeletal muscle atrophy and fat lipolysis. As an inhibitor of NF-κB signaling, Pyrrolidine dithiocarbamate (PDTC) was reported to relieve cancer cachexia; however, its mechanism remains largely unknown. In our study, we showed that PDTC attenuated cancer cachexia symptom in C26 tumor bearing mice models in vivo without influencing tumor volume. What’s more, PDTC inhibited muscle atrophy and lipolysis in cells models in vitro induced by TNFα and C26 tumor medium. PDTC suppressed atrophy of myotubes differentiated from C2C12 by reducing MyoD and upregulating MuRF1, and preserving the expression of perilipin as well as blocking the activation of HSL in 3T3-L1 mature adipocytes. Meaningfully, we observed that PDTC also inhibited p38 MAPK signaling besides the NF-κB signaling in cancer cachexia in vitro models. In addition, PDTC also influenced the protein synthesis of skeletal muscle by activating AKT signaling and regulated fat energy metabolism by inhibiting AMPK signaling. Therefore, PDTC primarily influenced different pathways in different tissues. The study not only established a simple and reliable screening drugs model of cancer cachexia in vitro but also provided new theoretical basis for future treatment of cancer cachexia.